2017
DOI: 10.1097/md.0000000000008488
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of STAT3 and VEGF expression for molecular diagnosis of lymph node metastasis in breast cancer

Abstract: Background:Axillary lymph node metastasis is associated with increased risk of regional recurrence, distant metastasis, and poor survival in breast malignant neoplasm. Expression of signal transducer and activator of transcription 3 (STAT3) is significantly associated with tumor formation, migration, and invasion in various cancers. In addition, vascular endothelial growth factor (VEGF) expression could promote angiogenesis and increase the risk of tumorigenesis. To determine correlations among STAT3 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
(19 reference statements)
2
4
0
Order By: Relevance
“…Seems clear the ability to improve the tumor spread by the lymph nodes microenvironment, which reinforce the importance of its removal along with that of the tumor, is a way to avoid its local or distant recurrence. Our finding is also in accordance with literature that postulate that cancer cells infiltrated in lymph nodes and surrounding macrophages as well, continues to produce VEGFs ligand and receptors molecules even in metastatic field, which enhance the aggressiveness of the tumors and their potential of continuing dissemination of malignant cells [29,30].…”
Section: Discussionsupporting
confidence: 93%
“…Seems clear the ability to improve the tumor spread by the lymph nodes microenvironment, which reinforce the importance of its removal along with that of the tumor, is a way to avoid its local or distant recurrence. Our finding is also in accordance with literature that postulate that cancer cells infiltrated in lymph nodes and surrounding macrophages as well, continues to produce VEGFs ligand and receptors molecules even in metastatic field, which enhance the aggressiveness of the tumors and their potential of continuing dissemination of malignant cells [29,30].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, VEGF expression was higher in NSCLC tumors compared with the tumor-adjacent normal tissues, and CCL25 treatment upregulated the expression of VEGF-C and -D in lung cancer cell lines, which could be blocked by the anti-CCR9 antibody. The aforementioned results were consistent with previous cancer-related studies on VEGF (47,48).…”
Section: Discussionsupporting
confidence: 93%
“…Our group and others previously demonstrated that STAT3 is an essential mediator of endothelial activation by directly inducing VEGF and HIF1a gene expression ( 116 , 117 ). On a functional level, STAT3 signaling has been reported to promote angiogenesis in human pancreatic, lung, and breast cancers ( 118 120 ) and we have previously shown that STAT3 is a critical regulator of the pro-angiogenic functions of myeloid cells in mice ( 121 ). In ovarian cancers, the expression of VEGF and its receptors VEGFR1 and VEGFR2 significantly correlate with pSTAT3 levels in patient samples ( 122 ), and STAT3 and VEGF have been shown to reciprocally regulate each other’s expression and activation in EOC models ( 123 , 124 ).…”
Section: Cd44 and Stat3 In Ovarian Tumor Microenvironmentmentioning
confidence: 96%